The Effect of Trading Volume Activity, Profitability and Solvability on Stock Returns: (Study on Banking Companies Listed on the Indonesia Stock Exchange for the Period 2019-2022) - Risma Julkismayana; Ni Made Adi Erawati (International Journal of Economics, Commerce, and Management, 2025)
This study aims to obtain empirical evidence regarding the effect of trading volume activity, profitability and solvency on stock returns. This study analyzed 122 samples of banking companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The samples were selected through purposive sampling method and analyzed using multiple linear regression. The results of the study indicate that trading volume activity has no effect on stock returns, profitability has a positive effect on stock returns and solvency has a negative effect on stock returns. The theoretical implications of this study are able to confirm the signal theory based on the hypothesis tests conducted. The practical implications of this study provide knowledge and can be used as consideration for companies regarding financial management policies and as considerations for investors regarding investment decision making